Mechanistic Investigation of the Domino Oxy-Cope/Ene/Claisen Reaction and Its Application to the Synthesis of Desdimethyl Ambliol B - Barriault, Louis; Denissova, Irina; Goulet, Nathalie (Synthesis, 2012)
We report an efficient and highly diastereoselective oxy-Cope/ene/Claisen reaction for the synthesis of decalin frameworks possessing four contiguous stereogenic centers. A detailed mechanistic investigation and its application to a short and protecting group free synthesis of desdimethyl ambliol B are presented.
Keywords: oxy-Cope/ene/Claisen; domino; sigmatropic; diastereoselectivity; macrocycle